2009
DOI: 10.1007/s00011-008-8151-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by cigarette smoke of macrophage function against Leishmania donovani infection

Abstract: Low concentration of cigarette smoke extract (CSE) counteracts L. donovani infection-mediated suppression of macrophage function without affecting host cell viability. This study reveals a new role of cigarette smoke extract (CSE) as an activator of macrophage function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Additionally, others have shown the macrophage viability remains relatively high after tobacco smoke exposure (low doses only), however, macrophage inflammatory functions (e.g. oxidative stress production/cytokine release) are activated due to the exposure conditions (Maity et al, 2009). Our results agree with these findings and may provide a pathway for altered inflammatory disease progression due to both heightened inflammatory responses and a depletion of inflammatory cells, both which could lead to inflammatory disease responses.…”
Section: Kupffer Cell Viability and Densitysupporting
confidence: 93%
“…Additionally, others have shown the macrophage viability remains relatively high after tobacco smoke exposure (low doses only), however, macrophage inflammatory functions (e.g. oxidative stress production/cytokine release) are activated due to the exposure conditions (Maity et al, 2009). Our results agree with these findings and may provide a pathway for altered inflammatory disease progression due to both heightened inflammatory responses and a depletion of inflammatory cells, both which could lead to inflammatory disease responses.…”
Section: Kupffer Cell Viability and Densitysupporting
confidence: 93%
“…Activated macrophages exhibit increased adhesion to and spreading over substrates, altered phagocytic activity and increased ROS generation (Bilitewski et al, 2008). Studies have demonstrated that different drugs and bioproducts induce macrophage activation (Pereira et al, 2005;Lopes et al, 2006;Morrow et al, 2007;Maity et al, 2009;Tiwari and Kakkar, 2009). The present study tested whether KA, which is a secondary metabolite produced by fungi, induces macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this study constitutes the first report about antileishmanial potentialities of Capsicum and Nicotiana genera. Capsicum frutescens L. extracts showed antiparasitic activity against a fish ectoparasite (Ling et al ., ), and a pre‐treatment with cigarette smoke extract from Nicotiana caused a decrease in parasite burden of Leishmania donovani ‐infected macrophages (Maity et al ., ). In the case of B. cestroides and C. nocturnum , no studies of these species have been found.…”
Section: Resultsmentioning
confidence: 97%